The correlation between loneliness and substance use proclivity in child and adolescent substance users - Kayaoglu, Kubra; Okanli, Ayse; Budak, Funda Kavak; Aslanoglu, Eren (Taylor & Francis Inc, 2022)
Purpose: The study was designed to determine the relationship between loneliness and substance use proclivity in child and adolescent substance users. Method: The study was conducted at the Substance Abuse Treatment Center for children and adolescents (CEMATEM) of a psychiatric hospital. A descriptive characteristics form, the UCLA Loneliness Scale, and the Substance Use Proclivity Scale were used to collect the data. The percentage distribution, arithmetic mean, and Pearson's Correlation tests were used to analyze the data. Results: The results of this study revealed that both the loneliness total mean and substance use proclivity total mean scores of the participants were 22.16 +/- 2.49 (high) and 28.91 +/- 1.76 (high), respectively. A statistically significant and positive correlation was also found to exist between the participant's total mean scores of the loneliness and substance use proclivity scales (p < .01). Practice implications: The lonelier the pediatric and adolescent patients participating in the study felt, the higher their substance use proclivity became.
Keywords: Adolescent; children; loneliness; substance use